2018
DOI: 10.1186/s12913-018-3603-y
|View full text |Cite
|
Sign up to set email alerts
|

Developing a comorbidity index for comparing cancer outcomes in Aboriginal and non-Aboriginal Australians

Abstract: BackgroundComorbidity is known to increase risk of death in cancer patients, both Aboriginal and non-Aboriginal. The means of measuring comorbidity to assess risk of death has not been studied in any depth in Aboriginal patients in Australia. In this study, conventional and customized comorbidity indices were used to investigate effects of comorbidity on cancer survival by Aboriginal status and to determine whether comorbidity explains survival disparities.MethodsA retrospective cohort study was undertaken usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…For instance, the mortality rate is substantially higher among cancer patients with comorbidities (47%) compared with cancer patients without comorbidities (34%) [19]. Given the clinical significance of comorbidity and its high prevalence in cancer survivors, it is essential to have a measure for quantifying likely effects on cancer outcomes [20]. Understanding more about comorbidities among cancer patients can generate possible evidence as well as provide direction for prevention, management, and treatment of chronic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the mortality rate is substantially higher among cancer patients with comorbidities (47%) compared with cancer patients without comorbidities (34%) [19]. Given the clinical significance of comorbidity and its high prevalence in cancer survivors, it is essential to have a measure for quantifying likely effects on cancer outcomes [20]. Understanding more about comorbidities among cancer patients can generate possible evidence as well as provide direction for prevention, management, and treatment of chronic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…There was a consistent pattern of poorer survival among Aboriginal and Torres Strait Islander peoples for seven ( 3 , 6 , 30 , 31 , 34 36 ) state-based studies that reported unadjusted estimates ( Table 3 ; Supplementary materials Table S1.5 ). Of the six studies that also reported estimates adjusted for various combinations of potential explanatory factors (other than age or sex), five found that the disparity reduced in magnitude after adjustment for remoteness, SES, and either cancer stage at diagnosis ( 34 36 ), or broad cancer group ( 6 , 30 ) although it was still elevated and statistically significant. However, the remaining study, over an earlier time-period with less complete cultural identification, found that the adjusted differential was only elevated in magnitude and statistically significant up to one year after cancer diagnosis ( 31 ).…”
Section: Resultsmentioning
confidence: 78%
“…The majority (n=27) of studies reported cause-specific survival while three reported relative survival ( 4 , 5 , 39 ). Most studies focused on short to medium-term survival while seven did not specifically provide this information about length of follow-up ( 34 36 , 39 , 40 , 44 , 47 ). A variety of statistical models were used to quantify the survival differential by Aboriginal and Torres Strait Islander status and suggest associative factors ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Of the 30 studies which reported on COPD (including the three studies which combined asthma and COPD),15 37 38 a single study reported community cross-sectional data,39 while the remainder reported on referred populations (table 3). Fourteen studies reported on patients presenting to hospital,29 33 37 38 40–44 53 54 57–59 12 on patients referred to a respiratory health service,7 14 15 30 45 46 48–52 60 and one each on patients using DOT,47 patients newly diagnosed with lung cancer,34 and patients diagnosed with obstructive sleep apnoea 61. The combined mean age of participants was 52.5±15.3 years,30 34 39 42 46 57 which varied by geography, with participants from the largest NT, CA study with a mean of 45.2±15.8 years,42 Kimberley region participants 51.8±9.3 years,39 from the largest NT, TEHS region study 51.3±12.3 years,46 SA participants 57.7±15.6 years34 and WA participants 54±15.4 years 57.…”
Section: Resultsmentioning
confidence: 99%